Project-based Method in Teaching Foreign Language for Specific Purposes - Bolsunovskaya L. M. Ludmila Mihailovna; Chris Phillips; Korotchenko T. V. Tatiana Valerievna; Matveenko I. A. Irina Alekseevna; Strelnikova A. B. Anna Borisovna; Ulyanova O. S. Oksana (2015, 2015)
Title screen